SEPARATION OF A MULTICOMPONENT SYSTEM FORMED IN THE PRODUCTION OF EPICHLOROHYDRIN - E. A. Okhlopkova; L. A. Serafimov; A. V. Frolkova; P. P. Tsekin (Тонкие химические технологии, 2016)
Epichlorohydrin is an important product of the basic organic synthesis. One promising direction of epichlorohydrin manufacturing is the liquid-phase epoxidation of allyl chloride with an aqueous solution of hydrogen peroxide in an organic solvent, methanol, in the presence of a heterogeneous catalyst, a titanium-containing zeolite. The multicomponent system of epichlorohydrin production according to this method contains allyl chloride, methanol, water, epichlorohydrin, 3-chloro-1,2-propanediol, 3-chloro-1-methoxypropanol-2 and hydrogen peroxide. In this work the thermodynamic topological analysis of the phase diagram of this multicomponent system of epichlorohydrin production was performed. On the basis of this study a principal technological scheme of separation of the studied system containing five distillation columns and a Florentine vessel was proposed.